2007
DOI: 10.1016/j.jphotochem.2006.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl radical-induced photochemical formation of dicarboxylic acids from unsaturated fatty acid (oleic acid) in aqueous solution

Abstract: In this study, we assess under laboratory controlled conditions the direct and hydroxyl radical ( OH)-induced photochemical production of low molecular weight (LMW) dicarboxylic acids and related compounds (C 2 -C 9 ) (DCAs) from oleic acid (cis-9-octadecenoic, 9C 18 ) in aqueous solution. Nitrate (NO 3 -)-amended and unamended oleate solutions were irradiated under ultraviolet-B radiation (UV-B, 313 nm) for 5 h, with NO 3 -being the source of OH. The OH-induced photochemical production of DCAs (C 2di -C 9di )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 34 publications
1
36
0
Order By: Relevance
“…The photochemical oxidation of these precursor organic compounds upon their emission from the surface ocean to the MABL can lead to formation of LMW‐diacids (from oxalic to succinic acids). As mentioned earlier, the photooxidation experiments of oleic acid by Matsunaga et al [1999] and Tedetti et al [] (publications from Kawamura's group) documented the formation of azelaic acid (which is being dominant among other diacids) and other diacids from oxalic to suberic acids. Likewise, the photooxidation experiments of azelaic acid solution by Yang et al [] have observed the formation of adipic acid as an intermediate secondary diacid which in turn subjected further photooxidation resulted its next lower homologues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The photochemical oxidation of these precursor organic compounds upon their emission from the surface ocean to the MABL can lead to formation of LMW‐diacids (from oxalic to succinic acids). As mentioned earlier, the photooxidation experiments of oleic acid by Matsunaga et al [1999] and Tedetti et al [] (publications from Kawamura's group) documented the formation of azelaic acid (which is being dominant among other diacids) and other diacids from oxalic to suberic acids. Likewise, the photooxidation experiments of azelaic acid solution by Yang et al [] have observed the formation of adipic acid as an intermediate secondary diacid which in turn subjected further photooxidation resulted its next lower homologues.…”
Section: Resultsmentioning
confidence: 99%
“…The hydroxyl radical‐induced photooxidation experiment of oleic acid by Tedetti et al [] showed the production of C 2 to C 9 diacids with azelaic acid being the dominant species followed by C 8 , C 7 , and C 6 diacids. However, they suggested that lower diacid homologues from oxalic to suberic acids are photochemical oxidation products formed from azelaic acid [ Tedetti et al , ]. More recent study by Yang et al [] also demonstrated that photooxidation of azelaic acid results in the formation of oxalic to suberic acids, with succinic and glutaric acids as dominant intermediates, which are eventually converted to their lower homologues (viz., oxalic and malonic acids).…”
Section: Resultsmentioning
confidence: 99%
“…44,45 Under these conditions, aqueous half-lives of PAEs decrease considerably and ranging between 2.4 and 12 years and 0.12−1.5 years for DEP and DEHP, respectively. 46 Under light irradiation, PAEs react with photogenerated OH • to form 4-hydroxy phthalate esters that present potential toxicity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Photochemical production of dicarboxylic acids and related compounds under controlled laboratory conditions has been reported (Hatakeyama et al 1985;Tedetti et al, 2007). Based on field experiments, Kawamura and Ikushima (1993) reported enhanced concentrations of C 2 -C 6 diacids in urban aerosols in summer.…”
Section: Introductionmentioning
confidence: 99%